Network analysis of blue carbon governance process in Indonesia - Ayostina, I.; Napitupulu, L.; Robyn, B.; Maharani, C.; Murdiyarso, D. (Elsevier, 2022)
To align with international climate efforts to remain within 1.5 degrees of the earth temperature, Indonesia requires concerted measures from actors to preserve and restore carbon rich ecosystems, especially blue carbon ecosystem. Although studies have suggested the importance of blue carbon ecosystems in contributing to Indonesian climate action, translating science to policy remains a challenge. Mapping actors and the pattern of information exchange related to blue carbon can help identify potential barriers in the blue carbon governance process and policy development. This study uses Social Network Analysis and integrates it with results from in-depth qualitative evaluation of institutional respondents. Data is obtained through questionnaires and semi-structured interviews with representatives from a broad range of organizations. It was found that the actor who oversees the fulfilment of the climate commitment, which is the most common objective of the network, is not a central actor. Second, the actors with the highest degree of centrality received little trust from other actors. Third, overall, the network has low quality ties. Each of these hinders knowledge providers’ ability to make an impact on policy development. By critically examining the interactions between actors, this research casts new light on the overlooked problem of the significance of the network in blue carbon governance process.